Window averaging to create LBP features for a color image - Ghazi M. J. Qaryouti; Monzer M. Krishan; Monther A. Kanan; E. Ziad M. Alasmer (Bulletin of Electrical Engineering and Informatics, 2022)
Digital color images are widely used in various computer applications. Some of these applications such as digital image recognition systems require dealing with image classifiers which can be formed as a set of values representing the image. In this paper a simple method of image features victor creation will be proposed, the method will be tested and implemented, the obtained experimental results will be analyzed to ensure that each generated features victor is unique. The proposed method will be based on a window averaging, the window size can be easily changed without affecting the features victor size.